Thank you for the opportunity to help you with your question!
(a-b)^2 = a^2 -2ab + b^2
compare with the expression
w^2 -14w + ---- -------1
a^2 -2ab + b^2 ------------2
The last term is b^2 which is missing in 1
Here a = w and
2ab = 14w => 2bw = 14w => 2b = 14 => b =7
So the last term is b^2 = 7^2 = 49
Perfect square expression will be w^2-14w+49
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?